The effect of local mycorrhiza isolated, Rhizobium and fertilization on zea mays and groundnuts plant productivity under field condition in Sudan - M.M., Alsamowal; Hadad, M. A.; Elhassan, G.A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The study was performed to test the effects of isolates local mycorrhizal fungi from date palm, alfalfa and sugarcane plants on zea maize plants growth traits (plant height, top dry weight, root dry weight, color rating, root colonization and tissue content of nitrogen, potassium and phosphorus). Also, the effects local and alien strains of Rhizobium, and isolated local mycorrhiza (VAM) on groundnut plant growth traits were studied. The use of VAM enhanced growth and development of maize plants. VAM isolated from date palm enhanced the performance of maize plants and improved all traits tested over the uninoculated plants and controls. AM fungi and Rhizobium positively affected groundnuts plant growth traits and nutrient. The performance of the AMF alone or in combinations with Rhizobium strains was significantly better than that of the bacteria alone in terms of plant height, top dry weight and root dry weight.